Kualitas Laminasi Bambu Betung (Dendrocalamus asper) pada Berbagai Perlakuan Ukuran Sortimen dan Buku Bambu - Putri Rafika Wulandari; Luthfi Hakim; Tito Sucipto (Program studi Kehutanan USU, 2015)
Laminated boards made from bamboo betung (Dendrocalamus asper) with the influence of different sizes and the presence of node sortimen. The purpose of this study was to evaluate the physical and mechanical properties of laminated bamboo betung, evaluating the effect of nodes and size sortimen the physical and mechanical properties of laminated bamboo board betung and determine the best size and the existence of the book sortimen bamboo as laminate raw material. Testing the water content, water absorption, delamination and bending strength is based JAS standard SE-7 2003 on Flooring surfaces while bonding strength testing is done based on ISO standard ISO 16981-2012. The results show the quality of bamboo betung laminate board meets the standards JAS-7-2003 SE for testing moisture content, delamination, but for testing water absorption does not fulfilling. On the mechanical properties of bamboo betung laminated board meets the standards JAS-7-2003 SE for testing bending strength and meets ISO 16981-2012 standards for surface bonding strength testing. The best treatment for laminated boards are laminated boards without involving nodes with a size of 20 cm sortimen.Keyword : Dendrocalamus asper, node, sortimen size, laminated board